A new memductance-based fractional-order chaotic system and its fixed-time synchronisation. (April 2021) - Dutta, Maitreyee; Roy, Binoy Krishna
Highlights: We propose a new memductance-based fractional-order chaotic system. For some typical values of initial conditions, it shows coexisting attractors whose topological structure changes on variation of its parameter. Synchronisation between two identical proposed systems as the master and slave systems is achieved in the presence of disturbances and parameters uncertainties by using terminal sliding mode control (TSMC).. Through switching between synchronisation and anti-synchronisation, the performance of the algorithm is shown. Abstract: Through this manuscript, the intentions of the authors are to present a new memductance-based fractional-order chaotic system. The new chaotic system shows coexisting single to double wings attractors for some typical values of initial conditions. Furthermore, a fixed-time convergence technique is applied for synchronisation between two identical proposed chaotic systems as the master and slave systems. This synchronisation technique is robust against bounded disturbances and parametric uncertainties. Through switching between synchronisation and anti-synchronisation, the performance of the algorithm is shown. The simulation results reveal the satisfactory performance of the algorithm.